Effects of tapping systems on mineral nutrients of latex total solids of RRIM 600 - Luo Xuehua; Cai Xiujuan; Liu Yunqing; Wu Juqun; Zhou Bixia (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.299-304.)
Five tapping systems were compared to observe their effects on the four kinds of mineral nutrient (nitrogen, phosphorus, potassium and magnesium) of the latex total solids of RRIM 600 tree. The results showed that: (1) the content of phosphorus and magnesium in each tapping system had no significantly difference between October and August, but the content of nitrogen and potassiun in October was remarkably higher than that in August (besides the s/2d/3 system). (2)In terms of the lost total mineral nutrient quantity flowed out along with the latex when the rubber tree produced 1kg dry rubber, the order of tapping system was : (S/4 + S/4)d/4+ET>(S/4 + S/4) d/5 + ET>(S/4 + S/4 d/6 + ET > s/2d/3 + ET > s/2d/2. In terms of the single mineral nutrient, the lost nitrogen and the potassium were higher than the phosphorus and the magnesium significantly. (3) The lost mineral nutrient was remarkarbale different between the upward tapping for morning latex. But for the late drip latex, the lost mineral nutrient under downward tapping was more than the upward tapping significantly, mainly for the lost potassium of the late drip latex under downward tapping was increased largely, and the lost potassium was the most of the four kinds of mineral nutrient. (4) For the tapping system of (S/4 + S/4)d/4, the highest yield of each tapping and the highest yield per tree cost the highest mineral nutrient lost through tapping.
Keywords: Mineral nutrient; Rubber tree; Tapping system; Total solids